Emotional competencies as a mediator of parental stress and overload in grandmothers who care for grandchildren (Salud, Arte y Cuidado, 2026)
Main Objective: To analyze the mediating effect of emotional competencies on parental stress and burden in grandmothers who care for their grandchildren. Methodology: An explanatory study was designed using a non-probabilistic sample of 200 grandmothers who care for their grandchildren. The Emotional Competencies Scale for Grandmothers, the Parental Stress Index, and the short version of the Zarit Burden Interview were applied. Correlations and a mediation model were estimated. Main Results: The women had an average age of 57 years; most were married, had completed high school, and were homemakers. On average, they cared for four school-aged grandchildren for 47 months, five days a week, and approximately 30 hours per week. It was observed that caring for more grandchildren was associated with higher emotional competencies, whereas more hours of care were linked to lower emotional competencies and higher parental stress. Emotional competencies significantly mediated the relationship between the number of grandchildren and caregiver burden, as well as parental stress, acting as a protective factor. Full mediation was found in both cases, highlighting its key role in well-being. Conclusion: This finding underscores the importance of strengthening emotional resources in this population group, as they enable better adaptation to the caregiver role and help reduce the negative effects associated with the time and intensity of care.
Keywords: caregivers; emotional competencies; parental stress; burden